Effectiveness of Kiambang (Salvinia molesta) and Kayu Apu Dadak (Azolla pinnata) Plants in the Phytoremediation System of Tofu Wastewater - Andi Gita Tenri Sumpala; Christine Elia Benedicta; Fachruddin Azwari; Kemala Hadidjah; Arini Rajab; Christopaul Pala'langan Toding Layuk; Martha Ekawati Siahaya; Adi Supriadi (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2026)
Soybean wastewater contains high levels of organic pollutans, such as high COD, TSS, and TDS values. This study aims to evaluate the effectiviness of phytoremediation using two aquatic plants species, Salvinia molesta and Azolla pinnata, in reducing pollutant levels in soybean wastewater. The experiment was conducted in a batc system using 10-liter plastic conyainers filled with 5 liters of soybean wastewater and 200 grams of each plant spesies. The study was cinducted over 7 days with samples taken on days 1, 3, and 7. The parameters measured included temperature, pH, dissolved oxygen (DO), total suspended solids (TSS), total dissolved solids (TDS), and chemical oxygen demand (COD). The results showed that Azolla pinnata significantly reduced COD levels by 65,91%. Overall, phytoremediation using Azolla pinnata demonstrated higher efficiency in improving water quality and could serve as a cost-effective and environmentally friendly treatment option for soybean wastewater.